Effect of Capital Investment and Population Growth on Unemployment Rate in West Java Province 2019-2023 - Lestari, Dwi Ayu Lestari; Nurichwan, Rahmawati (Indonesian Journal of Economics and Management, 2025)
West Java is the most populous province in Indonesia and contributes significantly to the national unemployment rate. The region’s unemployment rate has fluctuated annually, showing a stagnant trend without significant change. This study aims to: (1) examine the effect of capital investment on the open unemployment rate in West Java from 2019 to 2023; (2) analyze the effect of population density on the same; and (3) evaluate their simultaneous effects during the period. The study applies panel data regression analysis to explore the unemployment phenomenon across 27 cities and regencies in the province. Variables analyzed include capital investment, population density, and the open unemployment rate, processed using EViews 12 software. The findings indicate that capital investment significantly reduces the open unemployment rate. On the other hand, population density does not have a significant individual effect. However, both variables jointly influence the open unemployment rate in West Java during the period under study.